Characterisation of odour-active compounds in lupin flour. - Bader-Mittermaier, Stephanie; Czerny, Michael; Eisner, Peter; Büttner, Andrea (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Lupin ingredients are promising alternatives to soybean products owing to their similarly high protein content. Lupin flour exhibits a green and bean‐like off‐flavour in higher amounts. The aim of this study was to characterise and identify the main odour‐active compounds in lupin flour. RESULTS: The orthonasal aroma of lupin flour was evaluated by means of aroma profile analysis and was found to be characterised by grassy‐green, metallic, fatty, fruity, hay‐like, cheese‐like, and meat‐like odour qualities. Volatile compounds of lupin flour of Lupinus angustifolius cv. Boregine were extracted with dichloromethane and isolated by solvent‐assisted flavour evaporation. Aroma extract dilution analysis (AEDA) was carried out with the obtained extract. In total, 50 odorants were detected by high‐resolution gas chromatography–olfactometry. AEDA revealed 26 odour‐active compounds with flavour dilution factors higher or equal to 32. The substances were unequivocally identified by their odour characteristics, their retention indices and their mass spectra using one‐dimensional or two‐dimensional gas chromatography–mass spectrometry, respectively. CONCLUSION: A series of unsaturated and saturated aldehydes, ketones, carboxylic acids, alkyl‐methoxypyrazines and terpenes were identified for the first time as odour‐active contributors to the aroma of lupin flour. Copyright © 2009 Society of Chemical Indust